2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) induces peripheral blood abnormalities and plasma cell neoplasms resembling multiple myeloma in mice. (January 2019) - Wang, Lei; Kumar, Munish; Deng, Qipan; Wang, Xu; Liu, Ming; Gong, Zhaojian; Zhang, Shanshan; Ma, Xiaodong; Xu-Monette, Zijun Y.; Xiao, Min; Yi, Qing; Young, Ken H.; et al.
Abstract: Although epidemiologic studies have suggested a possible association between occupational exposures to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) and the risk of development of multiple myeloma, definitive evidence in support of this association is lacking. In the present study, we employed the Vk*Myc mouse model of multiple myeloma to assess the impact of TCDD exposure on multiple myeloma pathogenesis. TCDD induced splenomegaly and multiple peripheral blood abnormalities, including anemia and high serum IgG levels. In addition, TCDD triggered bone lytic lesions, as well as renal tubular casts, a phenomenon associated with human myeloma kidney disease. Even in wild-type C57BL/6 mice, TCDD increased serum IgG levels, induced anemia, and increased plasma cell presence in the spleen and bone marrow, hallmarks of benign monoclonal gammopathy. Lastly, TCDD induced AKT activation and the DNA damage response, key pathogenic events in myeloma pathogenesis, in animal spleen and/or bone marrow. These data indicate that TCDD accelerates monoclonal gammopathy development and promotes progression to multiple myeloma in genetically-predisposed mice. This work offers the first direct experimental evidence establishing TCDD as an environmental risk factor for monoclonal gammopathy of undetermined significance and multiple myeloma. Highlights: TCDD accelerated benign monoclonal gammopathy and multiple myeloma in genetically predisposed Vk*Myc mice. TCDD increased serum IgG levels and induced anemia in wild-type C57BL/6 mice, hallmarks of benign monoclonal gammopathy. TCDD triggered key pathogenic events in multiple myeloma progression.